“A land whose stones are iron...”—Iron ore sources in the Southern Levant - Eliyahu-Behar, Adi; Ben Dor, Yoav; Brauns, Michael; Shulman, Oriana Adi; Avni, Yoav; Killebrew, Ann E.; Tirosh, Ofir; Yahalom-Mack, Naama (Frontiers in Environmental Archaeology, 2023)
Recent discoveries of iron production remains in multiple Iron Age sites throughout the southern Levant indicate the significance of iron production in the region during this time.However, one main question remains unanswered -that is, provenance: Where were the iron resources located? Were they local or brought from afar? Answering these questions embodies great potential for reconstructing iron-ore procurement strategies and exploitation practices in their social, political, and economic context of the early 1st millennium BCE southern Levant.It has long been assumed that iron ore, prevalent in the earth's crust, is widely available.However, since high-grade ore was required for the smelting technology of the time, the bloomery process, only selected iron ore deposits in the region were suitable. This study aims to identify and characterize enriched iron ore sources in the southern Levant, chemically and isotopically. Samples were collected from sedimentary and hydrothermal sources and analyzed for their iron content, trace elements composition, and osmium isotopic ratios. Here we present the results of this preliminary investigation, introducing several substantial ore sources in the region and demonstrating the possibility of differentiating between these sources based on their chemical and Os isotopic composition. Finally, hematite objects from selected Iron Age archaeological sites are compared against the analyzed ore sources, showing inconsistency with the sampled ores.